1999
DOI: 10.1128/aac.43.5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Trovafloxacin, Ofloxacin, and Ciprofloxacin against Streptococcus pneumoniae in an In Vitro Pharmacokinetic Model

Abstract: An in vitro pharmacokinetic model was used to simulate the pharmacokinetics of trovafloxacin, ofloxacin, and ciprofloxacin in human serum and to compare their pharmacodynamics against eightStreptococcus pneumoniae strains. The MICs of ofloxacin and ciprofloxacin ranged from 1 to 2 μg/ml. Trovafloxacin was 8- to 32-fold more potent, with MICs of 0.06 to 0.12 μg/ml. Logarithmic-phase cultures were exposed to peak concentrations of trovafloxacin, ofloxacin, or ciprofloxacin achieved in human serum after 200-, 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…21,22 Pharmacodyamic studies with various fluoroquinolones against S. pneumoniae using in vitro pharmacokinetic models have shown that an AUC/ MIC ratio in the range of approximately 30 to 60 is sufficient to achieve eradication. [23][24][25][26][27] For quinolone-susceptible strain ATCC49619, tosufloxacin showed bactericidal activity, given that the AUC 0-24h /MIC ratios at 150 mg t.i.d. and 300 mg b.i.d.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 Pharmacodyamic studies with various fluoroquinolones against S. pneumoniae using in vitro pharmacokinetic models have shown that an AUC/ MIC ratio in the range of approximately 30 to 60 is sufficient to achieve eradication. [23][24][25][26][27] For quinolone-susceptible strain ATCC49619, tosufloxacin showed bactericidal activity, given that the AUC 0-24h /MIC ratios at 150 mg t.i.d. and 300 mg b.i.d.…”
Section: Discussionmentioning
confidence: 98%
“…It was suggested that AUC/MIC ratios of 30-60 were sufficient to eradicate S. pneumoniae. [5][6][7][8][9] However, because fluoroquinolones kill bacteria in a concentration-dependent manner, 4 not only the AUC/MIC but also the C max /MIC might affect their pharmacodynamics. Therefore, it was important to consider the effect of the AUC/MIC ratio and the C max /MIC ratio on the pharmacodynamics of fluoroquinolones against S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agreed with the ideas from previous PK/PD studies in which AUC/MIC ratios of approximately 30 to 60 were sufficient for the eradication of S. pneumoniae. [5][6][7][8][9] Resistance selectivity is one of the important PD factors in antibacterial agents. Pharmacokinetic parameters, as well as the target preference of quinolones, are thought to be associated with their resistance selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations